Model Sesar Pati di Jawa Tengah Berdasarkan Data GPS - Cecep Sulaeman; Pandu Adi Minarno; Imam Priambodo; Haunan Afif (Pusat Survei Geologi, 2020)
The campaign GPS surveyÂ was conducted in the 2017 - 208 by Centre for Volcanology and Geological HazardÂ Mitigation, Geological Agency for the purpose of studying the caracteristic of the Pati Fault. The complete processing and analysis of the GPS observations were performed using Gamit/Globk software version 10.6. Horizontally, displacement of GPS stations generally to the southwest and to the south with a velocity of 3.04 mm/yr up to 19.49 mm/yr. While the vertical displacement up and down with values varying from -125.60 mm/yr to 4.07 mm/yr. Base on displacement pattern of GPS stations by using Coulomb 3.3 softwaere, a Pati Fault model consist of three segments that have potensial produce earthquakes with moment magnitude Mw 6.2, Mw 6.2, and Mw 6.4 respectively.Keywords: GPS survey, Pati Fault, displacement, fault model.